LSD1 inhibition by tranylcypromine hydrochloride reduces alkali burn-induced corneal neovascularization and ferroptosis by suppressing HIF-1α pathway - Deng, Qian; Gao, Yuelan; Wang, Yujin; Mao, Jiewen; Yan, Yulin; Yang, Zixian; Cong, Yuyu; Yang, Yanning; Wan, Shanshan (Frontiers in Pharmacology, 2024)
Corneal neovascularization (CNV) is a sight-threatening condition with no effective treatment yet.Lysine-specific demethylase 1 (LSD1) has established significance in tumor angiogenesis regulation and is linked to multiple disorders caused by oxidative stress. Epigenetic control functions in the development of CNV, however, the role of LSD1 in CNV remains unclear. We established an alkali burn-induced CNV mouse model in vivo. Results show a substantial correlation between corneal damage and LSD1 levels. In addition, the effects of LSD1 inhibitor tranylcypromine hydrochloride (TCP) were examined through slit lamp, histological staining, and immunofluorescence. In addition, HIF-1α expression was also elevated after alkali burns, and subconjunctival injection of TCP reduced corneal inflammation and neovascularization. The expression of malondialdehyde (MDA), superoxide dismutase (SOD), and glutathione (GSH) levels were assessed in corneal tissues.Oxidative stress and ferrous ion expression during CNV were determined using 4-HNE, GPX4, and FerroOrange staining. Corneal alkali burns increased ROS levels and reduced antioxidative stress indicators, accompanied by elevated ferrous ion levels, which were reversed by TCP injection. In vitro, a hypoxia-reoxygenation (H/R) model was established using human umbilical vein endothelial cells (HUVECs) to study LSD1 or HIF-1α knockdown and lentiviral overexpression of HIF-1α. The effects on HUVECs migration, invasion, and angiogenesis were evaluated through cell scratching assay, transwell migration assay and tube formation assay. The role of ferroptosis was investigated using ROS staining, FerroOrange staining, and key ferroptosis proteins. The results of the in vivo experiments were further confirmed by the in vitro experiments. Further, The JAK2/STAT3 pathway's involvement in CNV regulation was explored through in vivo experiments with subconjunctival injection of AG490. Mechanistically, inhibition of LSD1 with TCP can alleviate corneal neovascularization through the JAK2/STAT3/HIF-1α pathway, reducing oxidative stress and ferroptosis, suggesting that LSD1 may be a possible therapy target.